99 film scenes for actors - Nicholas, Angela
Looking for a great piece to work on in your scene study class? For an audition? You want something fresh, juicy, well-written--something you haven't seen in every scene book. Give Chekov a rest and run to memorable characters and scenes from the silver screen.